A pilot study of the use of EEG-based synchronized Transcranial Magnetic Stimulation (sTMS) for treatment of Major Depression - Jin, Yi; Phillips, Bill (BMC psychiatry, 2014)
Background Repetitive Transcranial Magnetic Stimulation (rTMS) is an effective treatment for Major Depressive Disorder (MDD), and is based upon delivery of focal high-energy pulses of electromagnetic stimulation. We postulated that delivery of rTMS at the subject’s individual alpha frequency (synchronized TMS, or sTMS) would achieve efficacy with lower energy of stimulation. We developed a device that rotates neodymium cylindrical magnets at three locations along the midline above the subject’s scalp to impart low-energy, sinusoidal-waveform magnetic brain stimulation over a broad area, and performed this efficacy study. Method Fifty-two subjects with MDD were enrolled in a randomized, sham controlled, double-blind treatment study (Trial Registration: NCT01683019). Forty-six subjects were included in the final analysis. Most subjects received concurrent antidepressant medications that remained unchanged during the study. Subjects were randomized to three treatment groups: 1) active sTMS with a fixed frequency at the subject’s alpha frequency; 2) active sTMS with a random stimulus frequency that varied between 8 Hz and 13 Hz; and, 3) sham sTMS. 20 half-hour sTMS sessions were administered 5 days per week for 4 weeks. Results Subjects with either fixed or random frequency active sTMS had statistically significantly greater percentage reduction in depression severity compared to sham (48.5% vs. 19.3%, respectively; p = 0.001). No significant difference was found between fixed and random groups (p = 0.30). No significant side effects were reported. Conclusions These results suggest that sTMS may be an effective treatment for MDD.